Correlation of 18F-FDG PET/MRE Metrics with Inflammatory Biomarkers in Patients with Crohn's Disease: A Pilot Study. (19th September 2017) - Domachevsky, Liran; Leibovitzh, Haim; Avni-Biron, Irit; Lichtenstein, Lev; Goldberg, Natalia; Nidam, Meital; Groshar, David; Bernstine, Hanna; Ben-Bassat, Ofer
Abstract : Background . To investigate the association between 18F-FDG (Fluorodeoxyglucose) PET (positron emission tomography)/MRE (magnetic resonance enterography) metrics with the inflammatory biomarkers fecal calprotectin and C-reactive protein (CRP) in patients with Crohn's disease (CD). Methods . This prospective pilot study was institutional review board (IRB) approved with informed consent obtained. Consecutive CD patients were referred to 18F-FDG PET/MRE. Patients in whom colonoscopy was performed and CRP and fecal calprotectin levels were measured were included. CRP and fecal calprotectin were regarded as positive for inflammation if they were greater than 0.5 mg/dl and 150 mcg/g, respectively. Correlation of quantitative variables was performed using the Pearson's correlation coefficient. Receiver operating characteristic (ROC) curves were drawn and the area under the curve (AUC) was calculated to evaluate the accuracy of PET and MRE metrics in determining the presence of inflammation evaluated by calprotectin and CRP levels. Results . Analysis of 21 patients (16 women and 5 men, 43 ± 18 years) was performed. Magnetic resonance index of activity (MaRIA) score had an AUC of 0.63 associated with fecal calprotectin and CRP. Adding apparent diffusion coefficient (ADC) and metabolic inflammatory volume (MIV) to MaRIA score resulted in an AUC of 0.92 with a cutoff value of 447 resulting in 83% and 100% sensitivity and specificity, respectively. Conclusion . The addition of ADC and MIV to the MaRIA score increases the accuracy for discrimination of disease activity in patients with CD. Trial registration number is 2015062.